Role of spirituality in enhancing work related attitude - Amy, Mardhatillah; Abdul Rahman, Shukran (IJSRP Inc., 2015)
Purpose: This paper explores the relationship between individual spirituality and work related attitude namely; job satisfaction, organizational commitment. The construct of spirituality use in the present study consists of two subscales including individual relationship with God or a higher power and individual relationship with self, community and the surrounding. This paper discuses having a meaningful work, and consider working as worship to God can enhance employee work related attitude. Method: 428 random sampling of staff in one of Islamic Higher learning institution were participated in this study trough the cross sectional design data collection. Five questions from spirituality well being scale were used to measure individual spirituality Finding: Result indicated that individual spirituality significantly related with job satisfaction and organizational commitment. Individual who experience good relationship with Allah, and know what the purpose in life is are more satisfied and committed toward their job. Implication: It is one of the first studies in contemporary management studies that analyze the important of spiritual element in the work setting .It is hope that this study may enhance the implementation of spirituality at the work place that can help employee to have a meaningful work